Current issues on digitalisation of controls in the financial and budgetary sphere - E. A. Isaev (Вестник университета, 2022)
Digitalization of control activities is a prerequisite for quality implementation of state financial control in the Russian Federation and effective interaction between all control bodies in order to prevent and combat violations in the financial and budgetary sphere. The article is devoted to the idea of introducing a new “digital control”. This solution is based on transferring the processes of interaction between control bodies and objects to a digital environment, which will allow to conduct a digital dialogue. The possible results of the departmental project in terms of the Federal Treasury control unit are considered. Current actions of government authorities in control (supervision) and oversight in the financial and budgetary sphere, as well as measures taken by the Federal Treasury in this area were analysed. It is concluded that digital transformation has in fact become a necessary condition for increasing the efficiency of control in the financial and budgetary sphere.